Overcoming the problems of translating vedic literature in indonesian language through sri aurobindo's vedic interpretation method - Holay, Rutvij; Maheswari, Prashanthy Devi; Ismagulova, Symbat; Rahayu, Ni Wayan Sri (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The Vedas are the earliest texts known to humanity. Given their status as an ancient text, as well as the loss of Vedic knowledge over the centuries, it is unsurprising that understanding them presents a significant challenge to modern readers, particularly in terms of their use of archaic language, symbols, and parables. As a result, there is a significant discrepancy between the interpretation of the Vedas by the Vedic people and by modern scholars. Meanwhile, in the modern era, Western scholars engage in research and translation of the Vedas without fully grasping their significance as perceived by the Rishis. This presents a challenge in attempting to comprehend the Vedic texts. Accordingly, the objective of any translation of sacred literature must be to bridge this interpretive gap and to retain the significance of the original words. Methods: In Hinduism, as some of the archaic words, some of which only appear once and constitute around 25% of the Vedas, disappeared from common usage, the method of translation and interpretation of these words was first developed by Yāska, and added on to by Sāyaṇa. It is therefore crucial to gain an understanding of, and to develop the skills of, these three individuals. Focusing on more recent times, Sri Aurobindo (who died in 1950) provided more practical and accessible guidance for the present era. His method of Vedic interpretation is a synthesis of linguistic proficiency as delineated in Nirukta, an appreciation for symbolism, and an understanding of psychological principles, thereby ensuring that the words of the Vedas retain their capacity to resonate with individuals on a personal level. Findings: This entails a comprehensive examination that encompasses a profound grasp of the symbolism, philosophy, and spiritual intent enshrined in the Vedas. Sri Aurobindo's approach integrates symbolic interpretation with a broad cosmic vision, thereby enabling the translator to capture the spiritual core of the sacred text while remaining faithful to its original context. Conclusion: Furthermore, this method considers the relevance and applicability of Vedic teachings in contemporary Indonesian culture.